Resource allocation algorithm based on non-cooperative game theory in uplink OFDMA multi-hop relay networks - Zheng XIANG; Xu-ming FANG; Peng XU (Tongxin xuebao)
Resource allocation issue in uplink OFDMA multi-hop relay networks was investigated.Firstly,with constraints such as maximum transmission power being imposed,a multi-cell optimization model for resource allocation in uplink OFDMA multi-hop relay networks was formulated.By applying non-cooperative game and pricing theories,the optimization is transformed into the case where power was independently allocated on each sub-channel.The existence and uniqueness of Nash equilibrium for power allocation model which was based on non-cooperative was proven,and accordingly a distributed algorithm was proposed.Simulation results show that,the proposed algorithm can improve the system throughput effectively while profoundly reducing total system transmission power,thus achieving much higher energy efficiency ratio.